2012
DOI: 10.1016/j.virusres.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Core protein-mediated 5′–3′ annealing of the West Nile virus genomic RNA in vitro

Abstract: Genome cyclization through conserved RNA sequences located in the 5' and 3' terminal regions of flavivirus genomic RNA is essential for virus replication. Although the role of various cis-acting RNA elements in panhandle formation is well characterized, almost nothing is known about the potential contribution of protein cofactors to viral RNA cyclization. Proteins with nucleic acid chaperone activities are encoded by many viruses (e.g., retroviruses, coronaviruses) to facilitate RNA structural rearrangements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 86 publications
1
22
0
Order By: Relevance
“…While some of these factors were shown to be essential for the viral life cycle and/or to interact with defined elements of the genomic RNA, their precise functions remained mostly uncertain. The DV NS3 protein (35), the WNV core protein (36), and the cellular La (37) were observed to support flavivirus 5=-3= RNA interactions in a similar way, as it was observed here with AUF1 p45 (Fig. 8B).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While some of these factors were shown to be essential for the viral life cycle and/or to interact with defined elements of the genomic RNA, their precise functions remained mostly uncertain. The DV NS3 protein (35), the WNV core protein (36), and the cellular La (37) were observed to support flavivirus 5=-3= RNA interactions in a similar way, as it was observed here with AUF1 p45 (Fig. 8B).…”
Section: Discussionsupporting
confidence: 78%
“…The viral core is not essential for RNA replication (39), and recombinant La was found to inhibit RNA synthesis in the in vitro viral replicase assay (40). As neither NS3, core, nor La were indicated to operate in concert with the viral polymerase, the RNA annealing activities of these proteins were proposed to contribute to virion assembly and morphogenesis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…RNA chaperones promote folding of RNA molecules either by preventing their misfolding or by resolving misfolded RNA species without ATP consumption (44, 45). The RNA chaperone activity of WNV capsid was mapped to the C-terminal RNA-binding region of the protein (43) and was proposed to facilitate long-range interactions in the viral genome (46). A hallmark of active RNA chaperone domains is a high content of basic residues that are structurally flexible, a property shared among all flavivirus capsid proteins; thus, capsid proteins from other members of the genus are expected to display the same RNA remodeling capacity.…”
Section: Rna-binding and Chaperone Activity Of Capsidmentioning
confidence: 99%
“…The involvement of viral or cell proteins in facilitating the 3′-5′ RNA-RNA interaction has been suggested. Binding of the promiscuous RNA-binding cell protein La (Vashist, Bhullar et al 2011), the viral C protein (Ivanyi-Nagy and Darlix 2012) and the viral NS3 protein (Gebhard, Kaufman et al 2012) to both the 3′ and 5′ RNA ends of flavivirus genomes has been reported. However, unless the proteins binding to each end of the RNA can interact with each other or one protein can bind simultaneously to both the 3′ and 5′ RNAs this does not seem to be a viable mechanism.…”
Section: Cell Proteins Involvement In Facilitating the 3′-5′ Rna-rmentioning
confidence: 99%